ANALISIS E-GOVERNMENT DI KANTOR KELURAHAN TALUMOLO KECAMATAN DUMBO RAYA KOTA GORONTALO - Sakbir (Jurnal Administrasi Negara dan Ilmu Pemerintahan, 2023)
This research aims to determine E-Government Based Public Services at the Talumolo Village Office, Dumbo Raya District, Gorontalo City. The method used in this research is descriptive qualitative. The research results show that e-government-based public services in the Talumolo Village Office, Dumbo Raya District, Gorontalo City are not optimal. The four e-government indicators measured, namely transparency, accountability, efficiency and participatory, show that electronic-based public services organized by the Talumolo Subdistrict Government have not been implemented well. This can be seen from inadequate facilities and infrastructure, such as the absence of special public service applications that can be accessed by the community as well as the unpreparedness of the Subdistrict Government and the community in using electronic-based public service applications.